2009
DOI: 10.1007/s12088-009-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical properties of lichenase from Clostridium thermocellum

Abstract: The recombinant enzyme lichenase of size 30 kDa was over-expressed using E. coli cells and purifi ed by immobilized metal ion affi nity chromatography (IMAC) and size exclusion chromatography. The enzyme displayed high activity towards lichenan and β-glucan. The enzyme showed no activity towards carboxymethyl cellulose, laminarin, galactomannan or glucomannan. Surprisingly, affi nity-gel electrophoresis on native-PAGE showed that the enzyme binds only glucomannan and not lichenan or β-glucan or other manno-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The decrease in activity in presence of EGTA indicated that Ca 2+ ions may be essential for enzyme activity as EGTA specifically binds and chelates calcium ions in 1∶1 molar ratio [35]. The catalytic activity was noticeably increased in the presence of Ca 2+ and Mg 2+ salts elucidating the fact that these metal cations may be needed as co-factors while the heavy metals especially Co 2+ , Hg 2+ , Cu 2+ and Ag + caused decrease in enzyme activity as shown for recombinant cellulases [36], [37].…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in activity in presence of EGTA indicated that Ca 2+ ions may be essential for enzyme activity as EGTA specifically binds and chelates calcium ions in 1∶1 molar ratio [35]. The catalytic activity was noticeably increased in the presence of Ca 2+ and Mg 2+ salts elucidating the fact that these metal cations may be needed as co-factors while the heavy metals especially Co 2+ , Hg 2+ , Cu 2+ and Ag + caused decrease in enzyme activity as shown for recombinant cellulases [36], [37].…”
Section: Resultsmentioning
confidence: 99%
“…The cells were lysed using a probe sonicator (Sonics & Materials, Vibra cell, 150 W, pulse rate: 5 s on/10 s off) for 20 min in an ice bath. Subsequently, 20 μL of each sample was separately mixed with 5 μL of loading dye and boiled for 4–5 min before loading onto the SDS-PAGE . Each sample (5 μL) and a pre-stained protein marker were loaded in the wells, and SDS-PAGE was run at 60–80 V. Following electrophoresis, the gel was stained and destained as per the standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 20 μL of each sample was separately mixed with 5 μL of loading dye and boiled for 4−5 min before loading onto the SDS-PAGE. 28 Each sample (5 μL) and a pre-stained protein marker were loaded in the wells, and SDS-PAGE was run at 60−80 V. Following electrophoresis, the gel was stained and destained as per the standard protocols. Gel Documentation system (BioRAD, USA) and Image Lab 5.2.1 software were used to observe and analyze the protein bands based on their respective molecular weights.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%